Choosing sensitivity to reduce X-ray dose in medical phase contrast imaging - Preusche, Oliver (Optics Express, 2018)
In medical X-ray imaging, phase contrast imaging is to measure refraction angles caused by the patient. The X-ray dose for a given image quality depends on the sensitivity of the setup, i.e. on the angular measurement range. Measurement ranges of existing phase contrast setups are either too high or too low for perfectly imaging a human finger in air: There is a gap in available measurement ranges, which prevents a reduction of X-ray dose. To fill the gap, this work proposes a novel variant of a Talbot-Lau interferometer. Instead of a single phase grating, it uses two phase gratings, each consisting of tiny prisms. The height of the prisms is an additional factor in the measurement range, which allows to fill the gap. The potential is a dose-reduction by a factor of 5.4 compared to Talbot-Lau setups of same post-patient length. Simulation results indicate a polychromatic visibility of up to 20%.<br
Keywords: Talbot and self-imaging effects; X-ray imaging; Gratings; X-ray interferometry; Phasenkontrast; Röntgen; Röntgen-Interferometrie; Talbot-Effekt; Talbot-Effect